2021
DOI: 10.1108/ara-08-2020-0121
|View full text |Cite
|
Sign up to set email alerts
|

The effect of audit engagement partner professional experience on audit quality and audit fees: early evidence from Form AP disclosure

Abstract: PurposeThe purpose of this study is to examine the effect of audit engagement partner's professional experience on audit quality. The authors also investigate the relationship between the audit partner's experience and audit fees in both Big 4 and non-Big 4 accounting firms.Design/methodology/approachSince the Public Company Accounting Oversight Board (PCAOB) officially enacted Rule 3211 in 2017, US accounting firms are required to disclose detailed information of engagement partners in Form AP (PCAOB, 2015b).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
2
9
0
4
Order By: Relevance
“…Thus, the author could conclude that the audit fee doesn't influence the audit quality of BPR ABC. It was also emphasized by the research of Mrs. Nanda as an academician, she found that audit fees didn't significantly influence the audit quality, which was in accordance with the prior research (Chen et al, 2019;Liu & Xu, 2021).…”
Section: Ms Meytasupporting
confidence: 78%
“…Thus, the author could conclude that the audit fee doesn't influence the audit quality of BPR ABC. It was also emphasized by the research of Mrs. Nanda as an academician, she found that audit fees didn't significantly influence the audit quality, which was in accordance with the prior research (Chen et al, 2019;Liu & Xu, 2021).…”
Section: Ms Meytasupporting
confidence: 78%
“…While (Daniels and Booker, 2011) research state that independence significantly impacts audit quality. Furthermore, on other variables such as work experience, which is associated with audit quality, a previous study conducted by (Rajgopal et al, 2021) showed that work experience had a positive and significant effect both partially and simultaneously, while research conducted by (Liu and Xu, 2021), shows that audit experience does not have a considerable impact on the quality of audit results. In carrying out the audit process, auditors need good knowledge and experience.…”
Section: Theoritical Reviewmentioning
confidence: 94%
“…Unfortunately, data on the above inputs at the office‐level are not publicly available, and some prior research has used non‐public data on hours of grades of labour of audit partners and managers (Hackenbrack & Knechel, 1997). Some recent studies have used data from LinkedIn to measure managerial resources (Lee et al, 2022; Liu & Xu, 2021). Our focus is on all resources available at the office‐level not just the number of audit professionals.…”
Section: Methodsmentioning
confidence: 99%